Giant dentigerous cyst in the maxillary sinus: A Case Report - Laquihuanaco Loza, Felipe Santiago (2023)
The biological process of odontogenesis is complex, where molecular and cellular mechanisms participate at forming dental structures. The alteration of these mechanisms can cause dentigerous or follicular cysts, which are pathologies with abnormal cavities lined by epithelium and with liquid or semi-liquid content, usually surrounded by a layer of connective tissue; always associated with the crown of included teeth, they are asymptomatic and of slow evolution, discovered radiographically as a unilocular image and radiolucent. The large ones are infrequent and their treatment consists of complete surgical removal.